The causes and levels of lower limb amputation in geriatric patients (Annals of Medical Research, 2021)
Aim: Lower limb amputations (LLA) are considered as a serious psychosocial condition. The causes of amputation in young persons are generally trauma, work accidents, or tumors, while in geriatric patients, it is mostly vascular problems. The aim of this study is to determine the causes and levels of LLA of geriatric patients in a tertiary care center.Materials and Methods: In order to conduct this study, information was obtained from the automation records of geriatric patients who underwent LLA in our clinic between the years 2014 and 2017. We divided our patients into three groups according to their ages. Group 1 consisted of those patients in the age group of 65-74 years, Group 2: 75-84 years, and Group 3: 84-95 years. We also classified our patients according to amputation causes and levels.We classified the patients as above-knee, transtibial, metatarsal, and toe amputation according to the level of lower extremity amputation.Results: Of the 96 patients included in the study, 70 were male (72.9%), and 26 (27.1%) were female. Group 1 consisted of 45 patients, group 2had 38 patients, and group 3 had 13 patients. It was observed that the most common cause of LLA was diabetic foot ulcers (65 patients), followed by ischemic foot as a cause of LLA in 25 patients. Moreover,4 patients were amputated due to a tumor, while amputation was performed in 2 patients as a result of a crush injury. It was observed that metatarsal and toe amputation was the most common amputation type according to amputation levels. (26 patients)Conclusion: As a result of our study, the most common cause of LLA in Geriatric patients was diabetic foot ulcers. Considering that lower extremity amputations cause severe morbidity and mortality in geriatric patients, it is crucial to identify these patients with preventive medicine practices.
Keywords: Amputation; diabetic foot; geriatric; level; lower limb